RUMAH TRADISIONAL DURI DAN BUGIS - ABIDAH, ANDI (FORUM BANGUNAN, 2012)
Duri and Bugis Traditional houses have lontang system.Function first until third lontang have diferent of this etnict. Ladder position of Duri houses are side main building while bugines houses of front main building difference function of lontang is caused by position ladder.